Cost assessment of pharmacotherapy applied to patients affected by COVID-19 under invasive mechanical ventilation in a general hospital - Walter C. SOUZA; Roberta G. PEIXE; Maria C. SODRÉ; Ana P. ANTUNES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To evaluate the profile of patients affected by COVID-19 who required invasive mechanical ventilation in relation to the prescription of anesthetics, neuromuscular blockers, sedatives, antimicrobials and anti-inflammatory drugs in a general hospital in Rio de Janeiro. The impact of the pandemic on the consumption and price variation of these drugs was also evaluated. Methods: A retrospective study in the form of a case series in which the inclusion criteria were: patients admitted to the intensive care unit between May and July 2020 with a diagnosis of COVID-19, with positive PCR laboratory test, submitted to invasive mechanical ventilation. Exclusion criteria were: patients under 18 years old. The drugs of interest were defined through a review of the literature produced in 2020, the analyzes were carried out in 5 phases: data collection carried out by the research pharmacists in prescriptions and in the consumption reports of the system used in the institution; identification of unit prices of drugs of interest; calculation of the overall cost of drug therapy for patients; calculation of cost in relation to drugs of interest; comparison of data referring to the interest group with data on complete therapy and identification of medications with greater financial prominence; identification of price variation in public purchases of medicines with the greatest financial prominence. Results: Eighteen patients were selected with a total cost of pharmacological treatment of U$ 49,602.24, with an average of U$ 2,755.68 ± U$ 2,425.31 per patient. The consumption of different therapeutic classes was observed, the most consumed items were enoxaparin, norepinephrine, meropenem, midazolam and rocuronium. These 6 drugs accounted for 43.3% of the total cost of pharmacotherapy and it can be seen that their prices increased by up to 1664.7%. Conclusions: The high consumption with the valuation of the observed items directly implied the high cost of therapy for these selected patients and the increased risk of drug shortages for the treatment, with reflections on the quality of care provided and on patient safety.